Genetic Diversity Of Age, Plant Height And Number Of Grain Per Panicle Characters Of F3 Generation Derived From Crossing Silopuk With Fatmawati Varieties - Hafnes Wahyuni; Etti Swasti; Yusniwati Yusniwati (JERAMI : Indonesian Journal of Crop Science, 2019)
This study aims to determine the population and genetic parameters of population F3 result of selection pedigri red rice crosses Silopuk with Fatmawati Superior Varieties using Augmented Design. Silopuk cultivars with red and inlaid rice characteristics while Fatmawati varieties with characteristics of large grain size, high production, high grain number, early age and white rice. The crosses are expected to produce high, large grain size, large amount of grain, maturity and color of brown rice. This research was conducted August-November 2016 at UPT Farm Faculty of Agriculture Andalas University. The genetic material used is the seed of the generation of F3 (F3-5, F3-12, F3-55, F3-95, F3-118, F3-122) derivatives of red rice crosses Silopuk with Fatmawati and the seeds of the two elders as a comparison with the experimental method using Augmented Design. The results of this study indicate the F3 population character number of filled grains per panicle is higher than the two parents with a wide range and other characters are between the two parents. The phenotypic diversity of flowering age characters in the F3-122 family is (2,41) and 1000 weight of pithy grains in the family F3-5 (2,31) ; F3-55(2,39) and F3-95 (3,49) relatively narrow. However, heritability in the broadest sense and genetic variability for all characters ranges from moderate to high and narrow to broad. Estimated genetic progress with 5% intensity in F3 population has high criteria for all characters (age of flowering, harvest age, plant height, stem length, total tillers, number of productive tillers, total grain / panicle, percentage of filled grains / panicle , total grain weight / clump and weight of filled grain / clump) except panicle length characters and 1000 grain weight of filled grains. Differential selection of population F3 with 10% selection intensity based on 1000 grain weight of pith grain, plant height and total grain weight per hill obtained 31 selected individuals. Selected individuals will be forwarded to the F4 generation